Effect of tear deficiency on the course of endotoxin-induced keratitis - Gaydamaka, T.B.; Rafalyuk, S.Ya. (Ukrainian Journal of Ophthalmology, 2026)
Background:In recent years, the problem of tear production disorders and dry eye syndrome (DES) has become increasingly important because of significant worldwide prevalence of DES. Purpose: To investigate the effect of decreased tear production on the course of endotoxin-induced keratitis in rabbits. Materials and Methods: Animals were divided into three groups: group 1 (controls; 7 rabbits), group 2 (keratitis-only group; 9 rabbits, 18 eyes), and group 3 (keratitis + dry eye model group; 10 rabbits; 20 eyes). The state of the cornea was scored by Draize criteria (the degree of corneal opacity, degree of corneal edema, degree of corneal infiltration and corneal fluorescein staining area) at preselected intervals (24, 48 and 72 hours) postinfection. Results: It should be noted that the analysis of clinical scores of corneal inflammation in the models of intrastromal endotoxin-induced keratitis in intact animals and in those with experimental dry eye showed that the clinical manifestations in the latter were more pronounced. Conclusion: Tear deficiency significantly contributes to corneal inflammation in animal models of keratitis. Within the observation period, mean corneal edema, inflammatory infiltration and fluorescein staining scores in the (dry eye + keratitis) rabbit model were 21%, 21% and 17%, respectively higher than those in endotoxin-induced keratitis in animals without dry eye.